The Difference Differentiation Makes: Extending Eisner's Account. Issue 1 (February 2014) - Blanken‐Webb, Jane
Abstract In this analysis Jane Blanken‐Webb extends Elliot Eisner's account of how learning in the arts contributes to the creation of mind. Drawing on the psychoanalytic theory of D. W. Winnicott, Blanken‐Webb argues that the acts of meaning making to which Eisner attends rely on a prior developmental achievement — namely, the establishment of self‐in‐relation‐to‐world. This prior development is important to recognize in order to appreciate all that is at stake and at play within acts of meaning making. To demonstrate this, Blanken‐Webb points to reverberations of an earlier process of psychological differentiation embedded within such acts that are crucial for aesthetic experience and that carry on a continual process of refinement of self‐in‐relation‐to‐world. While Eisner has a great deal to offer regarding the importance of providing students access to multiple forms of representation, this perspective adds that in doing so we are expanding on a foundation of self‐in‐relation‐to‐world, thus facilitating an educational unfolding that is much deeper than we typically recognize.